2006
DOI: 10.1177/0960327106074603
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation, upregulation of CD11b/CD18 expression on leukocytes and increase in circulating leukocyte-platelet aggregates in Indian women chronically exposed to biomass smoke

Abstract: The majority of households in rural India still rely on unprocessed solid biomass for domestic energy. The aim of this study was to investigate whether chronic exposure to biomass smoke causes activation of leukocytes and the formation of leukocyte-platelet aggregates. We conducted flow cytometric analysis of β2 Mac-1 integrin (CD11b/CD18) expression on polymorphonuclear leukocytes (PMN) and monocytes, and P-selectin (CD62P) expression on the platelets of 165 women from eastern India, who cook solely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…Therefore, the question arises whether the observed changes among the ragpickers are attributable to their occupation or to the higher level of indoor air pollution they experience due to biomass fuel use. This is especially relevant because we earlier reported a strong positive association between biomass smoke exposure and β 2 Mac-1 integrin and P-selectin expressions in Indian women having lower socio-economic status 13) . We tried to address this question by controlling for the impact of biomass smoke in multivariate studies, and the results still showed a positive association between the profession of ragpicking and levels of leukocyte integrin, platelet P-selectin, plasma TNF-α and IL-8.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, the question arises whether the observed changes among the ragpickers are attributable to their occupation or to the higher level of indoor air pollution they experience due to biomass fuel use. This is especially relevant because we earlier reported a strong positive association between biomass smoke exposure and β 2 Mac-1 integrin and P-selectin expressions in Indian women having lower socio-economic status 13) . We tried to address this question by controlling for the impact of biomass smoke in multivariate studies, and the results still showed a positive association between the profession of ragpicking and levels of leukocyte integrin, platelet P-selectin, plasma TNF-α and IL-8.…”
Section: Discussionmentioning
confidence: 90%
“…Besides, they depended more on biomass fuel for daily household cooking. Compared to LPG and other fuels, biomass burning causes higher levels of indoor air pollution, and biomass smoke contains very high amounts of particulate and gaseous pollutants that usually elicit pulmonary and systemic inflammatory responses 12,13) . Therefore, the question arises whether the observed changes among the ragpickers are attributable to their occupation or to the higher level of indoor air pollution they experience due to biomass fuel use.…”
Section: Discussionmentioning
confidence: 99%
“…In chronically biomass smoke-exposed Indian females, activation of circulating platelets, neutrophils and monocytes has been reported with high levels of leukocyte-platelet aggregates [22]. As a number of studies on ambient air pollution suggest that particulate pollutants increase fibrinogen levels, thus enhancing blood coagulation [23], it is plausible that biomass smoke exposure could be a risk factor for cardiovascular events.…”
Section: Characteristics and Toxicity Of Solid Fuel Usementioning
confidence: 99%
“…Surface expression of P-selectin initiates capture and rolling of circulating leukocytes over stimulated endothelium (Theilmeier et al 2002) and the formation of platelet-leukocyte conjugates (Yokoyama et al 2005). Increased levels of platelet-leukocyte conjugates have been demonstrated in Indian women who used biomass as cooking fuel, producing higher levels of PM, as compared to women cooking with a cleaner fuel (liquefied petroleum gas) (Ray et al 2006). In a panel study of 60 elderly subjects with coronary artery disease, Delfino et al demonstrated associations between soluble P-selectin levels and the mean 1 to 5-day concentrations of ambient finer particles (PM 0.25 and PM 2.5 ), but not the bigger PM 10 (Delfino et al 2009).…”
Section: Fig 1 Biological Pathways Linking Pm Exposure and Arterialmentioning
confidence: 99%